PENGARUH PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA PEGAWAI PADA KANTOR DINAS KESEHATAN KABUPATEN BIREUEN - Azhar Ishak (AL-ILMU, 2021)
This study aims to determine the effect of career development on employee job satisfaction at the Bireuen District Health Office. This research uses quantitative research. The population in this study were employees of the Bireuen District Health Office, with a total sample of 43 respondents. Data was collected by filling out a questionnaire, then the data was processed quantitatively. The results of the partial study (t-test) indicate that the career development variable (X) has a t-value of 3.165 while the t-table is 1.684. This means that tcount > ttable, then the results of the study reject Ho and accept Ha. So it can be concluded that partially career development variables affect employee job satisfaction at the Bireuen District Health Office. Based on the results of simultaneous research (f test) shows that the Fcount value is 5.027 with a significant level of 0.003, while the Ftable value is 4.08. Then it can be written Fcount > Ftable (5,027 > 4.08). The results of the study accept Ha and reject Ho, which means that career development variables simultaneously affect employee job satisfaction at the Bireuen District Health Office.